Jurisprudence in a globalized world - Fabra Zamora, Jorge Luis (Edward Elgar Publishing, 2020)
"In this unique book, leading legal scholars and philosophers provide a breadth of perspectives and inspire stimulating debate around the transformations of jurisprudence in a globalized world. Traditionally the central debates surrounding jurisprudence and legal theory are concerned with the elucidation of the particularities of state-law. This innovative book considers that this orthodox picture may no longer be tenable, given the increasing standardization of technologies, systems and information worldwide. Split across four thematic parts, this timely book provides a broad overview of the topic, followed by in depth analyses investigating the modifications to jurisprudence's methodological approaches driven by globalization, the concepts and theoretical tools required to account for putative new forms of legal phenomena, and normative issues relating to the legitimacy and democratic character of these legal orders. Chapters cover legal encounters with alterity in a post-monist mode, normative legal pluralism, relating law and power in a historical global context, cosmopolitan legitimacy and human rights and dignity in a corporate world. Jurisprudence in a Globalized World will be a key resource for students and scholars working in global transnational law, public international law and legal theory and philosophy"--